The Infusion of Moral Values in A Commercial Publisher English Textbook - Tasya Rahmania; Intan Pradita (Research And Innovation In Language Learning (RILL), 2022)
This research aims to examine the infusion of moral value in English textbooks for middle school in Indonesia. The data were collected through transferring and normalizing the written data from a commercial English textbook entitled: English on Sky 2 for SMP/MTs kelas VII to the Antconc software. The data were analyzed by using corpus based analysis. In order to employ this type of analysis, we used the AntConc corpus analysis software and using vocabularies adopted by previous researchers. The findings of this research showed that the moral values that are represented in this textbook there are two moral values, which are values toward others and values toward self. For values toward others, there are sub values such as conveying kindness, as example is being helpful, and keeping promise; showing respect, such as asking permission and apologizing; showing affection, such as giving compliments, showing close relation with God. Moreover, for moral values towards self such as conveying how to appreciate, accept, yourself.